Nursing Care for Reducing Bruising in Patients Receiving Enoxaparin Sodium - Thanakittummakul, Nayada (Journal of Nurses Association of Thailand Northern Office, 2021)
Abstract Bruising is a common complication in patients receiving Enoxaparin Sodium, a low molecular weight heparin anticoagulant. Bruising caused by increasing pressure on tissue or pinching a needle through skin. Which lead to breaking capillary blood vessels, pooled bleeding under the surface of skin, and then leaking into the surrounding interstitial tissues. These cause uncomfortable feeling in patients both physically and emotionally. Bruising directly affect patients’ image. Moreover, pain from bruises and injection may also cause anxiety. Some patients may refuse subsequent injections or discontinue treatment due to the loss of trust in the nursing ability. Therefore, nurses need to have knowledge and understanding of bruising among patients who receive Enoxaparin Sodium to reduce its side effects. This article aims to present information about incident of bruising, related factors, mechanisms, signs and symptoms, and nursing care for reducing bruising.